Ubiquitin–proteasome degradation of serum- and glucocorticoid-regulated kinase-1 (SGK-1) is mediated by the chaperone-dependent E3 ligase CHIP - Belova, Larissa (Portland Press Ltd., 2006)
SGK-1 (serum- and glucocorticoid-regulated kinase-1) is a stress-induced serine/threonine kinase that is phosphorylated and activated downstream of PI3K (phosphoinositide 3-kinase). SGK-1 plays a critical role in insulin signalling, cation transport and cell survival. SGK-1 mRNA expression is transiently induced following cellular stress, and SGK-1 protein levels are tightly regulated by rapid proteasomal degradation. In the present study we report that SGK-1 forms a complex with the stress-associated E3 ligase CHIP [C-terminus of Hsc (heat-shock cognate protein) 70-interacting protein]; CHIP is required for both the ubiquitin modification and rapid proteasomal degradation of SGK-1. We also show that CHIP co-localizes with SGK-1 at or near the endoplasmic reticulum. CHIP-mediated regulation of SGK-1 steady-state levels alters SGK-1 kinase activity. These data suggest a model that integrates CHIP function with regulation of the PI3K/SGK-1 pathway in the stress response.